(untitled) (The Journal of Geography Education in Africa, 2021)
The COVID-19 pandemic led in 2019 to a very rapid change in the mode of teaching activities globally, from dominantly face-to-face to almost entirely online. Although the initial emphasis in this rapid transition was on technical issues related to e-learning systems, software and internet access, it was also clear that online teaching requires different pedagogic approaches, as demonstrated through the use of online videos, discussion forums, social media as well as other ways of communication and learning engagement between teachers and students. In this process, consideration of the implications of online teaching for discipline-specific learning outcomes and modes of assessment has been very much an afterthought but is critical to address if a generation of informed and articulate global citizens is not to be lost. This paper reviews a range of different assessment types and styles, both individual and group, formative and summative, that can be employed under remote (online) teaching and learning environments, in the discipline of Geography and with a particular focus on the specific needs and challenges found in South Africa. The paper presents and discusses different types of assessment styles and considers their advantages and disadvantages from both teachers’ and students’ perspectives. With respect to the discipline of Geography, the COVID-19 pandemic and its necessitated change in teaching and learning mode may provide an opportunity for different and more innovative styles of assessment than have been previously considered.